Вплив сучасних змін у менеджменті персоналу на розвиток менеджменту продуктивності підприємства - Драган, Олена Іванівна; Тертична, Любов Іванівна (My University, 2020)
У статті розглянуто світові тренди в розвитку менеджменту продуктивності. Об’єктом дослідження є взаємовплив і взаємозв’язок менеджменту продуктивності із перспективними змінами у розвитку менеджменту персоналу підприємства. Досліджено традиційний підхід до управління продуктивністю операційної системи. Обґрунтовано алгоритм процесу управління продуктивністю операційної системи за 9 етапами. Охарактеризовано види продуктивності залежно від отриманого результату та витрачених ресурсів. Запропоновані показники продуктивності з урахуванням сфери діяльності в натуральних одиницях виміру. Досліджені резерви продуктивності операційної системи і резерви підвищення продуктивності праці. Обґрунтовано взаємодію і взаємовплив процесів менеджменту продуктивності з процесами менеджменту персоналу підприємства. Тому, що більшість цих HR-процесів є спільними для менеджменту персоналу і менеджменту продуктивності. The modern trends of development of management productivity as increase of business processes efficiency; increase of application of IT- technologies; investments in human capital; grant of high level of autonomy and personnel motivation are considered in the article. The object of the research is interinfluence and intercommunication of management of productivity with perspective changes in the development of personnel management of the enterprise. The objectives of increases of productivity development of society are analyzed in the cut: strategic and the nearest. The traditional approach to the productivity management of the operating system (enterprises). The algorithm of the process of management of the operating system (enterprises) the productivity after 9 stages is described. The types of the productivity are described depending on the got result and spent resources. The indexes of productivity taking into account the sphere of activity in natural units of measuring are offered. Backlogs of productivity operational of system and backlogs of increase of the labour productivity are investigated. Co-operation and interrelation of management processes of productivity with the processes of personnel management of the enterprise are explained. It is proved that for successful development of productivity management it is needed to take into account the trends of modern changes in the personnel management of the enterprises that take place under the act of changeable environment. Modern changes in the development of personnel management are connected with the work of different generations, requirements of flexible chart of work, by technologies of outsourcing, unique suggestions for hiring talented specialists, digitalization and automation of HR processes. Majority of these HR - processes is similar for the management of personnel and productivity management. Thus, for successful realization of productivity management it is needed to take into account the modern trends of development of personnel management with the aim of increasing the productivity and labour effectiveness.
Keywords: кафедра економіки праці та менеджменту; тренди; удосконалення; продуктивність; менеджмент персоналу; менеджмент продуктивності; trends; improvements; productivity; personnel management; productivity management